Rendered materials partly substitute inorganic nitrogen fertilizers and improve nitrogen recovery in maize production system - Bhupinder Singh Jatana; Christopher Ray; Christopher Kitchens; Patrick Gerard; Nishanth Tharayil (Nutrient Cycling in Agroecosystems, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Regulating the nutrient release rates from proteinaceous agricultural byproducts using organic amendments and its effect on soil chemical and microbiological properties - Bhupinder Singh Jatana; Christopher Kitchens; Christopher Ray; Nishanth Tharayil (Biology and Fertility of Soils, 2020)

Symbiont transmission and reproductive mode influence responses of three Hawaiian coral larvae to elevated temperature and nutrients - Rebecca M. Kitchen; Madeline Piscetta; Mariana Rocha de Souza; Elizabeth A. Lenz; Daniel W. H. Schar; Ruth D. Gates; Christopher B. Wall (Coral Reefs, 2020)

Field variability and vulnerability index to identify regional precision agriculture opportunity - Christopher W. Bobryk; Matt A. Yost; Newell R. Kitchen (Precision Agriculture, 2018)

Extreme weather and experience influence reproduction in an endangered bird - Brian E. Reichert; Christopher E. Cattau; Robert J. Fletcher; William L. Kendall; Wiley M. Kitchens (Ecology, 2012)
Extreme weather events, such as droughts and heat waves, are expected to become more severe and more frequent in the coming years, and understanding their impacts on demographic rates is of increasing interest to both evolutionary ecologists and conservation practitioners. An individual's breeding probability can be a sensitive indicator of the decision to initiate reproductive behavior under varying environmental conditions, has strong fitness consequences, and can be considered the first step in a life history trade‐off between allocating resources for breeding activities or self‐survival. Using a 14‐year time series spanning large variation in climatic conditions and the entirety of a population's breeding range, we estimated the effects of extreme weather conditions (drought) on the state‐specific probabilities of breeding and survival of an endangered bird, the Florida Snail Kite ( Rostrhamus sociabilis plumbeus ). Our analysis accounted for uncertainty in breeding status assignment, a common source of uncertainty that is often ignored when states are based on field observations. Breeding probabilities in adult kites (>1 year of age) decreased during droughts, whereas the probability of breeding in young kites (1 year of age) tended to increase. Individuals attempting to breed showed no evidence of reduced future survival. Although population viability analyses of this species and other species often implicitly assume that all adults will attempt to breed, we find that breeding probabilities were significantly

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)